The Use of the Malay Language in Writing Status on the Facebook Page “Aku Anak Iban” - Ramio, Rollin Smith; Banseng, Saripah; Handrianto, Ciptro (Peneliti.net, 2024)
This study was carried out to identify the use of Malay in writing statuses on the social media Facebook page “Aku Anak Iban”; analyse the factors of using Malay in writing statuses on social media on the Facebook page “Aku Anak Iban”; and describe the steps to overcome the use of Malay in writing statuses on social media on the Facebook page “Aku Anak Iban”. The methodology of this study is a qualitative study. The researcher used the observation method to observe the writing of 15 members of the Facebook page to answer the first objective. Next, the researcher conducted interviews with 15 informants to answer research questions objective two and objective three. The results of the study found that as many as 59 Malay words were used to write posts on the status of the Facebook page “Aku Anak Iban”. The highest frequency is the words ‟hati”, ‟maksud”, ‟manusia”, ‟tapi” dan ‟yang” which are three times and followed by the ‟akan”, ‟apalagi”, ‟cuma” and ‟sebab” with frequency twice. Interviews with research informants revealed three elements and three processes. The study's findings demonstrate that the first element is an effective communication tool, with good use and mastery of the Malay language and poor use and mastery of the Iban language. In conclusion, Malay language phrases are used on Facebook sites by social media users, resulting in code-mixing between Malay and Iban languages.